Pembuatan Virgin Coconut Oil (VCO) dengan Cara Fermentasi di Desa Gunung Megang Kecamatan Gunung Megang Muara Enim - Ita Emilia; Yunita Panca Putri; Dewi Novianti; Melly Niarti (Universitas PGRI Palembang, 2021)
ABSTRACTÂ Processing of coconut fruit in Gunung Megang Village, Gunung Megang Muaraenim District aims to produce pure oil or Virgin Coconut Oil (VCO) which is the result of processed fresh coconut fruit by fermentation without going through a heating process, no additional chemicals, dyes, and preservatives so that it can survive. as vegetable oil. The method in this research is experimental. The results showed that making VCO using 2 coconuts produced 100 ml of VCO while VCO using 3 coconuts produced 300 ml of pure oil. It is hoped that the use of coconut fruit is not only sold in the form of unprocessed fruit but coconut fruit can be processed into pure oil or Virgin Coconut Oil and can be developed more broadly through village entrepreneurship programs so as to increase people's income, especially the people of Gunung Megang Village.Â Keywords: virgin coconut oil, fermentation, gunung megang villageÂ